It's Complicated—Adolescent Grief in the Time of Covid-19 - Weinstock, Louis; Dunda, Dunja; Harrington, Hannah; Nelson, Hannah (Frontiers in Psychiatry, 2021)
Presently, there is a real possibility of a second pandemic occurring: a grief pandemic. There are estimated to be over 1 million children and young people experiencing bereavement because of Covid-19. Adolescent grief is unique due to bio-psycho-social factors such as increased risk-taking, identity-formation, and limited capacity for emotional regulation. In this article, we will argue that adolescents are at increased risk of developing complicated grief during the Covid-19 pandemic, and that it is vital that services are improved to recognize and address this need before secondary problems emerge, including anxiety, depression, and substance abuse. Complicated grief in adolescents is widely underrecognized and often misdiagnosed as a range of mental health problems, addictions, and offending behavior. For example, 25% of <20 year olds who commit suicide have experienced childhood bereavement, whilst 41% of youth offenders have experienced childhood bereavement; this is in comparison with only 4% of the general population. Many of the broader risk factors for complicated grief were already increasing prior to the Covid-19 pandemic, including increased loneliness amongst young people, and the collapse of collective structures to help people manage grief. We propose that this pandemic could be a catalyst for mental health professionals to support and nurture the caring communities emerging in this time as an essential resource to prevent the onset of a grief pandemic.